Hubungan Literasi Media dengan Persepsi Gender Siswa Sekolah Dasar - Nanang Martono; Elis Puspitasari; Laila Sabrina; Amalia Nur Ramadhani (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
This article describes the relationship between media literacy and gender perception of elementary school students. This research aims to describe gender perception based on the media literacy of elementary school students. This research was conducted using a survey method in two elementary schools in Purbalingga, Central Java, located far from the city center (outside). The population of this study amounted to 80 students. The sample used is a 100% saturated sample of the total population. The results showed that the tau Kendall correlation value of the two variables was 0.23 with a significance value of 0.03. This value indicates a positive relationship between media literacy and the respondent's gender perception. So, the higher the respondent's media literacy, the better the respondent's gender perception. Respondents' media literacy is formed through content and information from mobile phones, TVs, computers/laptops, radios, and newspapers or magazines. Respondents use mobile phones more often because accessing data is easy and fast. The content and information about the roles of men and women received by the respondents formed the respondent's gender perceptions